Comparative Analysis of the Performance of Using Kisdam Jumbo Bag with Portadam on Costs and Implementation Time as Dewatering - Banur Hudah Roseantoro; Adi Prawito (LPPM NAROTAMA UNIVERSITY, Indonesia, 2022)
Dewatering (drying work) is a civil work that aims to control water (ground/surface water) so as not to interfere/impede the process of implementing a construction work, especially for the implementation of structural parts that are in the ground and below the ground water level. Dewatering work is closely related to kisdam. kisdamis a temporary barrier or barrier between water and the construction site for irrigation construction There are several methods used in the implementation of a project, one of which is the conventional/jumbo bag kisdam method which is carried out at the project site. There is also a portadam/non-conventional kisdam method which is basically the same asa temporary barrier or barrier between water and the construction site but what distinguishes it is that the installation/application process is carried out in dry and wet places, then brought to the project site to be assembled into a unified structure. In this final project, the analytical data needed for the comparison of these two systems is secondary data. Secondary data is data obtained from the implementing party in the form of unit price analysis. In this final project, an alternative design for non-conventional design is planned by comparing the cost analysis and implementation time. With a comparative analysis of the performance of the kisdam jumbo bag method/conventional and kisdam portadam/non-conventional, the results obtained that the jumbo bag/conventional kisdam method requires implementation time of 63 days at a cost of Rp. 44,409,856, - and the portadam/non-conventional kisdam method takes 102 days to implement and costs Rp. 28. 084.442,-.